Deixis and Speech Acts of a Poem by Ali Ahmad Bakatsir on Drama Script Entitled “Audatul Firdaus” - Maftuh Ahmad; Rina Susanti (Institut Agama Islam Negeri Salatiga, 2021)
This article aims to describe the type of deixis and speech acts, as pragmatics studies aspects, found in a poem by Ali Ahmad Bakatsir, an Indonesian-born poet, on drama script entitled “Audatul Firdaus”. Audatul Bakatsir tells about Indonesian Independence which was as the result of Indonesian people’s fight not as the colonialists’ gift. This research is a library research with qualitative method. The results shows that there are five types of deixis and six types of speech acts. The former one consists of persona, space, time, discourse, and social. Moreover, the later one include locutionary, perlocutionary, illocutionary, assertive, expressive, and commissive.